Comparative study on microstructure and properties of nanocrystal and amorphous W–Si–B coatings. (April 2023) - Li, Wenhe; Gu, Wenshuang; Chen, Yuqiu; Gong, Jun; Pei, Zhiliang; Sun, Chao
Abstract: Crystalline and amorphous W–Si–B coatings with different Si contents were fabricated by magnetron sputtering. The influence of Si content on microstructure, mechanical and tribological properties of the coatings was evaluated. The results reveals that the crystalline W–Si–B coatings are nanocomposite structures consisting of nanocrystalline AlB2 -type WB2 grains and amorphous Si/Si3 N4 . Crystalline coatings with Si content of 4.7 at.% exhibits the maximum hardness of 35.8 GPa and better fracture toughness compared with pure WB2 coating, leading to the lowest wear rate of 1.3 × 10 −7 mm 3 /Nm. As for the amorphous W–Si–B coatings, the lower hardness of the coatings tends to lead to excellent fracture toughness, which gives rise to the low wear rate. The different enhancement mechanisms of both types of coatings are discussed in detail. Highlights: Crystalline and amorphous W–Si–B coatings were deposited by magnetron sputtering. The mechanical and tribological properties of the crystalline W–Si–B coating were improved by the doping of Si element. The amorphous W–Si–B coatings showed better fracture toughness and excellent wear resistance.